Hospital admission in high-risk pregnancies: the social representations of pregnant women - Regynara Moreira Rodrigues, Antonia; Paiva Rodrigues, Dafne; Moura da Silveira, Maria Adelaide; Gomes Paiva, Antonia de Maria; de Melo Fialho, Ana Virgínia; Azevedo Queiroz, Ana Beatriz (Journal of Nursing Referência, 2020)
Background: Hospital admission in high-risk pregnancies changes the routine and the way in which pregnancy is experienced. These changes must be taken into account during care planning and delivery. Objective: To identify high-risk pregnant women’s social representations of hospital admission during pregnancy. Methodology: An exploratory, descriptive study, guided by the social representations theory, was carried out in two maternity hospitals in Ceará, involving 68 hospitalized high-risk pregnant women, between July and September 2016. The word association test was used and data were analyzed using the Tri-Deux-Mots software, version 5.3. Results: Pregnancy was represented by the satisfaction to gestate a baby, anchored in the biological and social role of motherhood. High-risk pregnancy was perceived as a problematic situation with an uncertain outcome, surrounded by negative feelings. Hospital admission was interpreted as a place of pain and loneliness, but also of care and protection, expanding the possibilities for a favorable evolution. Conclusion: The evoked words reflect important meanings attributed to pregnancy in a context of a high-risk pregnancy that requires hospital admission.